Circulating tumor cells and circulating tumor DNA: What surgical oncologists need to know?. Issue 5 (May 2017) - Cabel, L.; Proudhon, C.; Mariani, P.; Tzanis, D.; Beinse, G.; Bieche, I.; Pierga, J.-Y.; Bidard, F.-C.
Abstract: As a result of recent progress in detection techniques, circulating tumor DNA (ctDNA) and circulating tumor cells (CTC) can now be accurately detected in the blood of most cancer patients. While these new biomarkers can provide a better understanding of key biological mechanisms underlying cancer growth and dissemination, they also open up a wide range of possible clinical applications in medical oncology, radiation oncology and surgical oncology. In this review, we summarize the results obtained with ctDNA and CTC together with their potential future clinical applications in the field of surgical oncology, with particular focus on the perioperative setting of various types of cancer. These applications include, but are not limited to, cancer screening, early diagnosis, prognostic assessment, evaluation and management of preoperative systemic or local therapies, post-surgical detection of minimal residual disease and early detection of cancer relapse.